2017
DOI: 10.18203/2319-2003.ijbcp20172741
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic susceptibility pattern of bacteria isolated from patients of respiratory tract infection in a tertiary care hospital of Central India

Abstract: Background: Respiratory tract infections are one of the commonest types of infections affecting the Indian population and are a significant cause of morbidity and mortality. To deal with multidrug resistance one should be armed with region specific data about the susceptibility patterns of antimicrobials. This study was planned to identify the common pathogens responsible for the respiratory tract infection and their antibiotic susceptibility patterns.Methods: Smears were prepared from the specimens and gram s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Gentamycin and amikacin were found to be sensitive to Pseudomonas as shown in the studies done by Mandal et al and Nepal et al whereas Dhakre et al showed ampicillin and piperacillin/tazobactam combination to be highly effective against Pseudomonas. 10,11,13…”
Section: Discussionmentioning
confidence: 99%
“…Gentamycin and amikacin were found to be sensitive to Pseudomonas as shown in the studies done by Mandal et al and Nepal et al whereas Dhakre et al showed ampicillin and piperacillin/tazobactam combination to be highly effective against Pseudomonas. 10,11,13…”
Section: Discussionmentioning
confidence: 99%